Representasi Spiritualitas dan Romantisme dalam Lagu Munajat Cinta Analisis Semiotika Roland Barthes - Adib Fikri Ghozali (PT. Nawa Edukasi Nusantara, 2025)
Music is a manifestation of human intellectuality and imagination combined with rhyme and tone as a means of conveying deep expression. This study analyzes the representation of spirituality and romance in the song Munajat Cinta by Ahmad Dhani and T.R.I.A.D. using Roland Barthes' semiotic approach. This qualitative descriptive study explores the denotative and connotative meanings in the song's lyrics to understand the messages contained therein. The results of the analysis show that this song represents the meaning of spirituality through an individual's relationship with God, such as prayer, surrender, and spiritual reflection. The lyrics reveal the meaning of tawakal and a sense of devotion to God as a source of strength. On the other hand, the dimension of romance is seen from the emotional expression of the struggle for love, trauma, and the desire for sincere love. Symbols such as